Regular Detection and Intelligent Monitoring Technology of Atmospheric Storage Tank Based on Acoustic Emission and Internet of Things - Jiehui Xie; Xueying Lu (e-Journal of Nondestructive Testing)
Acoustic emission testing is a non-destructive testing method that can